1185 Developing A Care Pathway For Insomnia In Older Adults And Adults With Dementia: Results Of A Consensus Meeting. (27th May 2020) - Benca, R; Ferziger, R; Wickwire, E M; Bertisch, S; Biddle, J; Boustani, M; Culpepper, L; Gooneratne, N; Lett, J; Manderscheid, R; Mehra, R; Reynolds, C; et al.
Abstract: Introduction: Insomnia among older adults and dementia patients carries a high public health burden. Yet, treatment is inconsistent or absent. Standardized, programmatic carepaths can be implemented in clinics/systems/communities to address this after tailoring to local environments. To determine what elements should be included, a consensus meeting was convened, which included discussion, voting on components, and further consensus-building among diverse stakeholders. Methods: Participants represented a wide range of stakeholders and specialties, including academic research, clinical care, industry, government, payors, sleep medicine, primary care, geriatrics, psychiatry, neurology, nursing, pharmacy, quality, and implementation science. 27 statements regarding key components of carepaths for insomnia in elderly and dementia populations were presented and discussed. These represented items addressing identification of patients, screening and assessment, deciding treatment modality and delivery, providing behavioral treatment, providing pharmacotherapy, addressing combined therapy, addressing comorbidities, and incorporating outcome evaluation. All N=20 participants voted individually whether they agreed or disagreed with each statement. Items were scored as 0=strongly agree, 1=agree, 2=disagree, and 3=strongly disagree. Mean scores were evaluated and responses were dichotomized to agree/disagree. Results: Despite diversity among attendees, median rate of agreement was 95% (IQR=85-95%). Mean score was 0.69 (SD=0.31). 95%CIs were computed for each proportion and compared to the mean. The following elements were significantly different from the mean (p<0.05): medication decision trees (M=0.25), accounting for comorbidities (M=0.26), include outcome evaluation (M=0.30), utilization of EMR (M=0.40), incorporate caregiver (M=0.42), and differ across parts of the system (M=1.79). Conclusion: Insomnia carepaths for older adults should address identification, screening and assessment, treatment decisions, treatment type and delivery, and evaluation. Organizations should consider these elements when designing carepaths for insomnia among older adults and dementia patients. Consensus-building should begin during the process of prioritizing care path components. Support: Merck Research Labs provided support